Perbedaan Humas Dan Kajian Lain - Viya Ananda Nur Sakdiyah; Ahmad Qowimun Nasheh; Amidanal Khikmah; Sinta Lutfiana; Chusnul Chotimah (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
In the current era, many institutions compete to build an image. Public relations (public relations) or what is usually called public relations (PR), is something that is familiar to every educational institution and institution outside of education. Public relations is one of the strategies in forming an institution's image, both positive and negative. This type of research method uses library research or library research. The results of the research The basic function of Public Relations (PR) is not to present the organization's views or public attitudes, but to reconcile or adjust to the public interest any personal aspect of the organization or corporate behavior that has social significance. So here PR functions to help organizations make adjustments to the environment in which the organization operates. The importance of the position of PR for the organization and for the organization's reputation. Political, social and technological changes in society at large, coupled with the emergence of a global economy, have increasingly confirmed the need for PR programs to be implemented. Through regular strategies at every level of business. What should not be forgotten is that every member of an organization is a representative of a company or organization, and all their behavior will reflect the overall image of the company or organization. By creating, implementing, monitoring and measuring a professional PR strategy, each organization can feel comfortable with itself, and employees or members of the organization will also feel comfortable with their leaders.